2018
DOI: 10.1183/23120541.00057-2018
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung abnormalities and physical function

Abstract: The term interstitial lung abnormalities (ILA) was coined to define a precursory stage of idiopathic pulmonary fibrosis and encompasses a set of radiological changes seen in interstitial lung diseases (ILD) but are often of lesser magnitude [1]. ILA have been associated with age, many environmental and genetic risk factors and pulmonary symptoms of idiopathic pulmonary fibrosis [1, 2]. ILA have also been associated with reduced exercise capacity and self-reported health and function [3–5].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…These findings are similar to those reported in other cohorts, such as COPDGene, ECLIPSE, and AGES-Reykjavik, where asymptomatic subjects with ILAs presented poor pulmonary function compared to clinically healthy subjects [ 2 , 19 , 20 ]. In addition, we compared the subpleural ILA pattern vs. HC, and the results were comparable with the whole ILA group, similar to the previous report by Axelsson et al [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…These findings are similar to those reported in other cohorts, such as COPDGene, ECLIPSE, and AGES-Reykjavik, where asymptomatic subjects with ILAs presented poor pulmonary function compared to clinically healthy subjects [ 2 , 19 , 20 ]. In addition, we compared the subpleural ILA pattern vs. HC, and the results were comparable with the whole ILA group, similar to the previous report by Axelsson et al [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…While associations with COPD differ, ILA have been positively associated with paraseptal emphysema, a subtype of emphysema that is not associated with airflow obstruction and is of largely unknown clinical significance [ 54 ]. What’s more, an increased risk of acute respiratory distress syndrome (ARDS) among critically ill patients in the intensive care setting has been linked with ILA [ 55 ], smokers with ILA have been shown to have decreased 6-minute walking distance [ 56 ] and participants with ILA in a general-population cohort had worse performance in various tests of decreased physical function and worse self-reported health and functional status than their peers [ 57 , 58 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…However, large cohort studies have reported prevalence of 2–10% [ 2 5 ] and a higher risk of mortality [ 2 , 6 ]. ILAs have been shown to be associated with symptoms including breathlessness, reductions in lung function [ 2 ] and exercise capacity [ 7 ] and genetic abnormalities common to familial interstitial pneumonia and idiopathic pulmonary fibrosis (IPF) [ 8 , 9 ]. A proportion of ILAs are known to progress to IPF, yet ILA prevalence exceeds that of IPF by a considerable margin.…”
Section: Introductionmentioning
confidence: 99%